Advanced wound healing with chitosan hydrogels incorporating metabolites from whale-derived Lactiplantibacillus plantarum HJ-S2 - Li, Yizhen; Tang, Xu; Liu, Yang; Chen, Xiaofeng; Wang, Ling; Su, Yanjun; He, Wei; Li, Jingjing; Huang, Qinmiao; Wu, Peng (Frontiers in Materials, 2025)
IntroductionTwo significant barriers to skin wound care are severe inflammatory cascade reactions and microbial infections. The metabolites of probiotics contain various components, such as lactic acid and bacteriocins, which can synergistically maintain skin microecological balance and promote wound healing and tissue regeneration through mechanisms.MethodsThis study utilized lactic acid bacteria isolated from the whale intestine. Inspired by the concept of the whale’s skin self-repair ability and the influence of gut microbiota on the skin, this study ingeniously utilized the acidic properties of the lactic acid bacteria fermentation broth to dissolve chitosan (CS), forming a hydrogel while simultaneously incorporating the cell-free probiotic metabolites (CFPM) of Lactiplantibacillus plantarum HJ-S2 into a stable three-dimensional network structure. Various characterizations were tested, including water content, swelling ability, rheological properties and degradability.ResultsThis resulted in the creation of a medical hydrogel capable of promoting skin wound healing, named PM@CS hydrogel. PM@CS hydrogel exhibited excellent swelling ability in different liquid environment. FT-IR analysis showed that the hydrogel is successfully crosslinked, and thermalgravimetric analysis showed that PM@CS hydrogel was stably degraded under high temperature. PM@CS hydrogel and CFPM of HJ-S2 strongly inhibited the growth of E. coli and S. aureus. The organic acid content of CFPM was analyzed by HPLC, revealing the lactic acid and acetic acid were produced in large quantities as two main organic acid metabolites that may contribute to the antibacterial efficacy. Beyond the outstanding antibacterial ability, application of PM@CS hydrogel led to rapid healing of burn wounds, and diabetic wounds.DiscussionThe results indicated that the whale-derived probiotics have significant potential for application in treating burns and scalds, particularly in the treatment of diabetic wounds.